The Effects of Learning Transfer on Clinical Performances Among Medical Staff: A Systematic Review of Randomized Controlled Trials - Tung, Yung-Chieh; Xu, Ying; Yang, Yu-pei; Tung, Tao-Hsin (Frontiers in Public Health, 2022)
Purpose This study aimed to evaluate the influence of learning transfer on the clinical performance of medical staff. Methods We searched PubMed, Embase, and the Cochrane Library for all associated studies without any language restrictions from the inception until 31 December 2021. Results This systematic review screened out 14 eligible studies that met the inclusion criteria. Most of these studies showed that learning transfer contributed to the clinical performance of medical staff. Through education, or when knowledge and skills have common basic principles, learning transfer will be more apparent than for those who learn by themselves and those without simulation training. Conclusions The findings of this review support an association between learning transfer and the clinical performance of medical staff. However, it was noted that due to the lack of relevant research and the major differences in the methods and indicators used in previous studies, we are restricted in conducting an effective meta-analysis. Further comprehensive trials will be needed to assess the impact of learning transfer on the clinical performance of medical staff. Systematic Review Registration PROSPERO, identifier: 341439.